2022
DOI: 10.3389/fimmu.2021.803014
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphonuclear Myeloid-Derived Suppressor Cells Are Abundant in Peripheral Blood of Cancer Patients and Suppress Natural Killer Cell Anti-Tumor Activity

Abstract: Tumor microenvironment (TME) includes a wide variety of cell types and soluble factors capable of suppressing immune-responses. While the role of NK cells in TME has been analyzed, limited information is available on the presence and the effect of polymorphonuclear (PMN) myeloid-derived suppressor cells, (MDSC). Among the immunomodulatory cells present in TME, MDSC are potentially efficient in counteracting the anti-tumor activity of several effector cells. We show that PMN-MDSC are present in high numbers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…have shown that exosomes derived from Tumor-associated macrophages up-regulate miR-192-5p to promote endometrial cancer cells apoptosis and effectively suppress the progression of endometrial cancer ( 60 ). Exosomes secreted by polymorphonuclear (PMN) myeloid-derived suppressor cells (MDSCs), which are immunomodulatory cells present in the TIME, significantly inhibit NK cell-mediated anticancer activity, suggesting that the detection of PMN-MDSC content may have prognostic value ( 61 ). miR-326 in M1 macrophage exosomes promotes apoptosis of liver cancer cells and inhibits cancer proliferation and migration by downregulating the expression of NF-κB in liver cancer ( 62 ).…”
Section: Discovery Of Exosomes and Their Roles In Cancer Progressionmentioning
confidence: 99%
“…have shown that exosomes derived from Tumor-associated macrophages up-regulate miR-192-5p to promote endometrial cancer cells apoptosis and effectively suppress the progression of endometrial cancer ( 60 ). Exosomes secreted by polymorphonuclear (PMN) myeloid-derived suppressor cells (MDSCs), which are immunomodulatory cells present in the TIME, significantly inhibit NK cell-mediated anticancer activity, suggesting that the detection of PMN-MDSC content may have prognostic value ( 61 ). miR-326 in M1 macrophage exosomes promotes apoptosis of liver cancer cells and inhibits cancer proliferation and migration by downregulating the expression of NF-κB in liver cancer ( 62 ).…”
Section: Discovery Of Exosomes and Their Roles In Cancer Progressionmentioning
confidence: 99%
“…Unfavorable responses can also be predicted, especially when the presence of other types of immune cells (e.g. MDSCs) are detected ( 25 ). Notoriously, in a number of specific cancers, non-malignant cells can far outnumber the malignant ones.…”
Section: Composition Of the Tmementioning
confidence: 99%
“…Myeloid-derived suppressor cells (MDSCs) are a heterogeneous group of immune cells originating from the bone marrow myeloid stem cell lineage, with a strong immunosuppressive function. MDSCs interact with other immune cells, including NK cells and T lymphocytes, to regulate their function, although their mechanisms of action have not been elucidated yet (Tumino et al, 2022). In cancer patients, the amount of MDSCs found in circulation are highly increased and it has been associated with an increased number of CTCs (Elbasateeny et al, 2022;Papadaki et al, 2021).…”
Section: Myeloid-derived Suppressor Cellsmentioning
confidence: 99%